Preparation and Characterization of a-SiC:H Absorber Layer for Semi-transparent Solar Cells. (December 2015) - Vygranenko, Y.; Fernandes, M.; Louro, P.; Vieira, M.; Sazonov, A.
Abstract: This paper reports on device-quality silicon-carbon alloy (a-SiC:H) application as an absorber material in semi-transparent solar cells. Films with an optical bandgap ranging from 2 to 2.3 eV were prepared by plasma enhanced chemical vapour deposition (PECVD). The n-i-p structures with undoped SiC:H layers deposited under the same experimental conditions were also fabricated and characterized. The optimized devices showed forward current-voltage characteristics with a diode ideality factor in the range from 1.4 to 1.8, and an open circuit voltage up to 0.92 V. The density of deep defect states in a SiC:H was estimated from the transient current measurements and correlated with the optical bandgap.